A. 3
B. 0
C. 1
D. 2
B
\({9^x} - {6^x} = {2^{2x + 1}} \Leftrightarrow {9^x} - 2.4{}^x = 0 \Leftrightarrow {\left( {\frac{3}{2}} \right)^{2x}} - {\left( {\frac{3}{2}} \right)^x} - 2 = 0\)
Đặt \({\left( {\frac{3}{2}} \right)^x} = t > 0\) thì \(t{}^2 - t - 2 = 0 \Leftrightarrow \left[ \begin{array}{l}
t = - 1(ktm)\\
t = 2(tm)
\end{array} \right. \Rightarrow {\left( {\frac{3}{2}} \right)^x} = 2 \Leftrightarrow x = {\log _{\frac{3}{2}}}2 > 0\)
Vậy phương trình không có nghiệm nào âm.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247